Developing Creative and Critical Thinking Skills Through Open Ended Design Projects at the Freshman and Senior Level - Tharakan, John (Journal of Engineering Education Transformations, 2018)
It is crucial that engineering students develop creative and critical thinking skills as part of the skill set needed to become real world problem solvers. Incorporating exercises that encourage and develop creative and critical thinking skills in students is essential for a syllabus to achieve outcomes that demonstrate adequate preparation of the student of engineering to face real world challenges. In this paper,we report on the inclusion of open ended design (OED) type projects that students work on in teams as part of the requirements for both a freshman level introduction to chemical engineering design course and for a senior level core chemical engineering course or kinetics and reactor design. The paper outlines the key components of such exercises and articulates on the specifics of how these are assigned to students, the process by which the students work in collaborative groups and teams to develop the openended solution and discourses on the rubric that students are provided so that they are aware of how the assessment and evaluation of their work will be conducted. The paper articulates on the components of the final report and presentations that the students teams are expected to develop and deliver. Finally, we discuss the student educational outcomes that are being appropriately addressed through such OED projects, and report on our experience in terms of the achievement of the highlighted outcomes by the students.